Managing small computer training premises: A case study on Pusat Komuniti Siber, Jitra - Abdul Mutalib, Ariffin; Mohd Elias, Ezanee; Abdul Wahab, Mohd Helmi (Faculty of Information Technology, Universiti Utara Malaysia, 2005)
There has been a vast number of training premises set-up and introduced lately for providing community with opportunity to continue learning. This is an advantage not only for their existence but also the fees are affordable even though by local communities. Well-managed training programs by considering the trainees, trainers, apparatus and teaching medium can contribute to the basis of producing K-Workers. A research has been conducted partly using TIER model to investigate whether the computer training program at Pusat Komuniti Siber (PKS), Jitra has been well managed using TIMO model and the results show that the mean after training program is far encouraging than the mean before training. This paper's objectives are to illustrate the training program - how the training is organized - and trainees' perception towards the training program. Other than that, this paper visualizes what is being done at PKS, Jitra.